The impact of Mentoring on Banks' employees' job satisfaction, job performance and job retention - Hii, Yew Leng (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Purpose -The main purpose of this study was to study the impact ofmentoring on banks' employees' job satisfaction, job performance and job retention in central region of Sarawak, namely in Sarikei and Sibu DiVision) Methodology -Questionnaires consisted of three parts were distributed personally to the banking staff at Sarikei and Sibu Division. The first part ofthe questionnaire is analyzing the demographic of respondents. The next two parts are attached with 18 each questions respectively reflected each individual dimensions of mentoring and its dependents. The data was analyzed by the SPSS Version 17.0 computer software. Findings -In this study, psychosocial support in mentoring was found significant in employees' job satisfaction, job performance and job retention with ~ = .66 with p<O.OI, ~ = .63 with p<O.OI and ~ ::;= .71 with p< 0.01 respectively. However, career support in mentoring was not significantly related to job performance, job satisfaction and job retention.